Diagnostic accuracy of visual triage checklist in early recognition of COVID-19 cases in the pediatric population: A retrospective cohort study - Ayesha Imtiaz; Abdullah Y. Akkam; Lulwah H. AlThumali; Ahlam M. AlHarthi; Honey G. Porte; Wesal S. AlOsaimi; Maha M. A. AlAsmari; Rawda B. G. Salih; Biswadev Mitra (BMC Pediatrics)
Abstract Background During the coronavirus disease 2019 (COVID-19) pandemic, healthcare facilities developed surveillance systems to identify patients suspected of having COVID-19 to segregate them during their hospital stay. As a part of this infection control strategy, the Ministry of Health in the Kingdom of Saudi Arabia developed a visual triage (VT) checklist for early screening and isolation of patients in the hospital. The aim of this study was to evaluate the diagnostic accuracy of this visual triage checklist in identifying children with COVID-19. Methods This was a retrospective, single center study that included all children who were tested for COVID-19 and were admitted to the hospital through the pediatric emergency department. The diagnostic accuracy of the visual triage checklist was assessed using COVID-19 PCR as the gold standard. Results A total of 1333 patients were included. The visual triage checklist had a sensitivity of 94.3% (95% CI: 87.2–98.1) and a specificity of 16.0% (95% CI: 14–18) with an area under the receiver operating characteristic curve of 0.55 (0.53–0.58). The positive predictive value of the checklist was low at 7.35% (95% CI: 5.9–9.0). Conclusion The VT checklist has high sensitivity, and is therefore potentially useful as an initial screening tool. However, the diagnosis of COVID-19 requires early secondary confirmation to avoid the large number of false positive cases associated with this tool.